Dormant Mycobacterium tuberculosis converts isoniazid to the active drug in a Wayne's model of dormancy. (November 2018) - Raghunandanan, Sajith; Jose, Leny; Kumar, Ramakrishnan
Abstract Isoniazid (INH) is one among the four first-line drugs used in the treatment of tuberculosis. The bactericidal activity of INH is due to its ability to inhibit mycolic acid synthesis, which is an integral component of the mycobacterial cell wall. Non-replicatingMycobacterium tuberculosis (MTB) is phenotypically resistant to INH. The exact mechanism of this resistance is not clear, although the inability of dormant MTB to convert the pro-drug into an active form is thought to be one of the possible reasons. Employing targeted metabolomics approach, we show that dormant MTB can metabolize INH into its active INH-NAD+ adduct form. Further we show that the dormant bacteria have unaltered gene expression levels ofkatG andinhA (INH metabolizing enzymes). Transcript levels of drug efflux pump proteins which were low during dormancy did not increase in response to INH treatment. These findings point to an alternative mechanism for INH resistance in dormant MTB, which needs to be further elucidated.